Creolization of Values: How Fair Taxation is Achieved for Everyone - Natalia Conroy (Journal of Economic Sociology, 2018)
Lotta Björklund Larsen’s new book is an ethnography written as a “social biography of things” which is not a rare case in modern Western anthropology. What makes this ethnography special is that the “thing” under study is a report by in-house analysts of the Swedish Tax Agency based on their own two-year research into errors made by small businesses in their annual tax returns. Of course, the anthropologist followed the Agency’s Task Force, not in order to understand why Swedish entrepreneurs make such mistakes, but to understand how the Agency obtains its information about tax compliance and uses it to motivate citizens to comply, and to what extent the Agency itself is shaped by taxpayers’ perceptions of fairness and by their ways of defining the boundaries between private and public and between household and business in everyday life. Björklund Larsen claims that, because of the law’s inconsistency, Swedish auditors work as the law’s interpreters and develop artistic skills to balance two different sets of values—“hard” and “soft.” Hard values of controllability are used to legitimate audits, soft values of empathy help to show society that the Agency collects a “fair” amount of money. Even though the Agency appears to have been very successful in this “creolization” of values over the last few decades, the balancing is always very political and risky, and, in order to save its reputation and to maintain the trust of society in most ambiguous situations, the Agency prefers not to rock the boat and to brush research results under the carpet. I would highly recommend Shaping Taxpayers to anyone interested in knowledge production, technology, and government studies.